2020
DOI: 10.17582/journal.jahp/2021/9.s1.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Azolla pinnata on Imidacloprid Induced Hepatorenal Toxicity, Oxidative Stress and Immunosuppression In Nile tilapia

Abstract: I midacloprid (IMI), a new generation of neonicotinoid insecticides, has a broad potential spread because of its agonistic effect on insects over vertebrates (Buszewski et al., 2019). From 2013 to 2015, the European Commission prohibited the use of three neonicotinoid pesticides including imidacloprid (Baroso, 2013). Because of their bioaccumulation in fish, insecticides are extremely dangerous to fish and other organisms in the food chain (Bojarski and Witeska, 2020). Fish is one of the non-target organisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In an in vitro experiment, Kunjiappan et al (2015) even found hepatoprotective effects of A. microphylla extract on common carp hepatocytes. Azolla pinnata supplementation can reduce oxidative stress in liver of tilapia (Attia et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro experiment, Kunjiappan et al (2015) even found hepatoprotective effects of A. microphylla extract on common carp hepatocytes. Azolla pinnata supplementation can reduce oxidative stress in liver of tilapia (Attia et al, 2021).…”
Section: Discussionmentioning
confidence: 99%